Clinical Case: Investigation of the Cerebral Blood Flow Alteration due to Intra-Aortic Counterpulsation Balloon Support in Early Postoperative Period - E. V. Aksonov; A. A. Beregovoj; R. B. Demchenko; D. V. Bondarets (Ukrainian Journal of Cardiovascular Surgery, 2019)
Introduction. Intra-aortic counterpulsation balloon support is a most common supportive therapy method which increases coronary and cerebral blood flow in patients with left-sided heart failure.The aim. To represent a clinical case of cerebral blood flow alteration due to intra-aortic counterpulsation balloon (IACPB) support in the early postoperative period.Methods. A 78-year-old patient with unstable angina, history of infarction (1998, 2002) and cardiosclerosis. EchoCG: contractile function of the left ventricle is drastically reduced, EF 32 %, moderate pulmonary hypertension 45 mm Hg. ECG: Sinus rhythm, sinus tachycardia, 110 bpm, subendocardial ischemia of the anterior left ventricle wall. Coronary angiography: left ventricle contractility is diffusely reduced, high occlusion of the right coronary artery, occlusion of the distal third of the circumflex branch of the left coronary artery (LCA), 90 % stenosis of the LCA. Taking into account the protracted attack of angina pectoris which was not relieved by narcotic analgesics, and taking into account total damage of coronary arteries in combination with diffuse decrease in contractile capacity of the left ventricle, the patient underwent preventive implantation of intra-aortic balloon pump, and aortic coronary artery bypass was performed on a beating heart.Results. The changes in general structure of EEG comprised increased theta activity in the central (hypothalamic) regions; increased alpha activity in central and parietal regions; reduction of total energy levels in left frontal lobe, left parietal and occipital regions.Conclusions. Pulse wave created by intra-aortic balloon pump increases cerebral blood flow and improves energy balance of the brain tissue in patients with left-sided heart failure.